Pengaruh Model Project Based Learning Terhadap Kemampuan Numerasi Peserta Didik Kelas IV UPT SD Negeri 197 Pinrang - Saleha, Saleha; Elihami, Elihami (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This research discusses "The influence of the project based learning model on the numeracy abilities of Class IV students at UPT SDN 197 Pinrang". This research aims to determine the numeracy abilities of class IV students at UPT SDN 197 Pinrang before being treated with the problem based learning model. To determine the numeracy abilities of class IV students at UPT SDN 197 Pinrang after being treated with the problem based learning model. And to find out the effect of the problem based learning model on the numeracy abilities of class IV students at UPT SDN 197 Pinrang. To solve the problem above, research was conducted. This research is a Quantitative Research with a Pre-Experimental Design approach with a One Group Pretest Posttest design which was conducted in 2024. This research used a sample of 27 respondents. Data collection techniques were carried out by observation, initial test (Pre-test), treatment, final test (Post-test) and documentation. The research was carried out in class IV UPT SDN 197 Pinrang. The data analysis technique used is the Parametric Statistical test. The results of this research show that the Pre-test score is an average of 63.93 from 27 student samples with a KKM of 70, meaning that the average student score on the Pre-test has not reached the minimum standard of completeness set. Meanwhile, the average post-test score is 87.83 with a KKM of 70, meaning that overall class IV students at UPT SDN 197 Pinrang have reached the set completion standards. The results of calculating the influence of the problem based learning model on students' numeracy skills in class V PPKn subjects at MIN 2 Jeneponto using parametric statistics and t-test show a significant influence which from the results of the t-test analysis (Paired Sample t-Test) with the final data obtained, namely tcount = 10.255 > ttable = 1.703 with a significance level of α = 0.05. From the values ​​explained above, the hypothesis Ho is rejected and Ha is accepted, meaning the influence of the problem based learning model on the numeracy abilities of class IV students at UPT SDN 197 Pinrang, this is proven by an average increase of 10.255 seen from the results of the Pretest and Posttest.